Gestión administrativa y su relación con la calidad de los servicios del club campestre Tarira, cantón Ventanas, año 2014 - Alvarado Yong, Yomaira Gissela (2015)
This present research was located at kilometer 23 via Quevedo- Ventanas in Club Campestre TARIRA. The main objectives were to investigate the following administrative management and its relationship to quality of services, since it is considered a significant change in recent years with the company, due to declining customer that this has had. The purpose pursued this research is to establish what is the relationship of the administrative management analyze the quality of the services provided by the Club Campestre TARIRA. The research hypothesis raised establishes whether the administration has relationship between service quality and if this is having shortcomings due to the administration that they handle. The descriptive methodology allow analyzing facts and events, between the administration and the relationship with the quality of services offered at the Club Campestral TARIRA, all this was made possible through an analytical research process, the same that welcomes different methods for conducting this research….